Research publications in the field of health: omission of hypotheses and presentation of common-sense conclusions - Turato, Egberto Ribeiro; Machado, Alexandre Cason; Silva, Douglas Fini; Carvalho, Guilherme Machado de; Verderosi, Natalia Reis; Souza, Thiago Ferreira de (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Medical literature should consist of knowledge applicable to profes- sional education; nevertheless, the profusion of articles in databases provokes disquiet among students. The authors considered the premise that scientific production in the field of health follows a mechanical description of phenomena without the clarity of motivating questions. The aim was to interpret material from expert reports, applied by medical students to analyze articles from renowned journals. DESIGN AND SETTING: This research project was exploratory, searching for latent meanings regarding methodological problems in a sample of papers. It was performed in a Brazilian medi- cal school. METHODS: The sample was intentionally built, consisting of articles related to original research in the field of health, published over the previous five years. The results came from text content analysis, performed by a professor and his medical students. RESULTS: (1) Failure to state a hypothesis is an equivocal practice: articles did not show clarity of hypothesis to demonstrate that their authors had epistemological knowledge of the methods chosen. (2) There is a certain belief that in normal scientific practice, hypotheses are unnecessary: studies without explicit hypotheses led to supposi- tions that they merely repeat dominant models. (3) Presentation of common sense as scientific conclusions: research brings together what would have mobilized the researchers initially. CONCLUSIONS: Absence of formal hypotheses leaves scientific production vulnerable when put under epistemological discussion. Conclusions from scientific articles are often confounded with common-sense statements. Quantitative research is suggested, for studying the frequency of occurrence of these dubious methodological points.